The role of timing in the development and evolution of the limb - Zhu, Meng; Tabin, Clifford J. (Frontiers in Cell and Developmental Biology, 2023)
The term heterochrony was coined to describe changes in the timing of developmental processes relative to an ancestral state. Limb development is a well-suited system to address the contribution of heterochrony to morphological evolution. We illustrate how timing mechanisms have been used to establish the correct pattern of the limb and provide cases where natural variations in timing have led to changes in limb morphology.